ANALISIS ANGGARAN BELANJA DAERAH SEBAGAI ALAT PENGENDALIAN PADA BADAN PENGELOLAA KEUANGAN DAN ASET DAERAH KABUPATEN BOMBANA - Sari, Ika Maya; Akib, Mulyati; Shesillia, Anggini (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACKThis Research aim to know difference of favourable dan unfavourable which is material among expense realization and budget at MonetaryÂ Body Organizer and Asset Area Sub-Province of Bombana. Methode Analysis the used is descriptive analysis. Result of this research indicate that Realization Budget (expens) in the year 2015 and 2016 categorized to profit (favourable) of amount of compared to slimmer realization of area budget which have been planned, so that can be said that monetary Office Body Organizer and Asset Area Sub-Province of Bombana have been able to do effectiveness of expense.Â Keywords: Budget, Control, Budget Variants